Antineoplastics for treating Alzheimer's disease and dementia: Evidence from preclinical and observational studies - Das, Viswanath; Miller, John H; Alladi, Charanraj Goud; Annadurai, Narendran; De Sanctis, Juan Bautista; Hrubá, Lenka; Hajdúch, Marián (Medicinal research reviews, 2024)
As the world population ages, there will be an increasing need for effective therapies for aging-associated neurodegenerative disorders, which remain untreatable. Dementia due to Alzheimer's disease (AD) is one of the leading neurological diseases in the aging population. Current therapeutic approaches to treat this disorder are solely symptomatic, making the need for new molecular entities acting on the causes of the disease extremely urgent. One of the potential solutions is to use compounds that are already in the market. The structures have known pharmacokinetics, pharmacodynamics, toxicity profiles, and patient data available in several countries. Several drugs have been used successfully to treat diseases different from their original purposes, such as autoimmunity and peripheral inflammation. Herein, we divulge the repurposing of drugs in the area of neurodegenerative diseases, focusing on the therapeutic potential of antineoplastics to treat dementia due to AD and dementia. We briefly touch upon the shared pathological mechanism between AD and cancer and drug repurposing strategies, with a focus on artificial intelligence. Next, we bring out the current status of research on the development of drugs, provide supporting evidence from retrospective, clinical, and preclinical studies on antineoplastic use, and bring in new areas, such as repurposing drugs for the prion-like spreading of pathologies in treating AD.
Keywords: Observational Studies as Topic; Alzheimer Disease; aging; Drug Repositioning; Humans; preklinické hodnocení léčiv; lidé; antineoplastic; neurodegenerative diseases; přehodnocení terapeutických indikací léčivého přípravku; zvířata; Animals; pozorovací studie jako téma; dementia; Alzheimerova nemoc; Antineoplastic Agents; drug repurposing; demence; Drug Evaluation, Preclinical; Alzheimer's disease; protinádorové látky; Dementia